National Alliance of Stakeholders in the Cereal Seed Sector in Morocco - Multistakeholder Workshop Report - Dhehibi, Boubaker; Boughlala, Mohamed; Moussadek, Rachid; Amri, Ahmed; Akramov, Kamiljon; Baum, Michael (2023)
On the 1st March 2023, the – Maroc (INRA), the International Center for Agricultural Research in the Dry Areas (ICARDA), and the Ministry of Agriculture of Morocco (MAPMDREF), organized a multi-stakeholder workshop "National Alliance of Stakeholders in the Cereal Seed Sector in Morocco". The agenda of the workshop is provided in Appendix 1. High-level policymakers, including Mr. Aziz Abdelali, General Director of the (SONACOS), a national seed marketing company, Mr. Belfadla Driss, President of the (AMMS), Dr. Faouizi Bekkaoui, Director of INRA and Dr. Abdelaziz Yasri, General secretary of INRA, attended the workshop (Table 1). More than 20 representatives of various stakeholders attended the workshop, including officials from the Ministry of Agriculture and agencies, researchers and non-governmental and non-profit organizations, and representatives of international organizations. This workshop aims to discuss the concrete measures that must be taken by the various stakeholders in a harmonized and coordinated manner to accelerate the dissemination and adoption of new resilient varieties of cereals developed locally.